Inovasi Slurry Ice Machine Indonesia/Mesin Pembuat Bubur Es (MPBE) Merah Putih Metode Scraped-Surface Berkapasitas 1,5 dan 0,5 Ton/Hari: Innovation of Indonesian Scraped-Surface Slurry Ice Machine with 1.5 and 0.5 Ton Per Day Capacity - Mahyudi; Nur Mahmudi Ismail; Eko Fajar Nurprasetyo; Ahmad Syihan Ismail; Esha Ganesha` SBW; Andrie Bayupati; Ibnu Susakti Idris (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Designing evaporator, condensor and electronic control were conducted to produce an innovation of slurry ice machine operated by 3-phase electricity. Result indicated that the machine start producing slurry ice within about 2 minutes, with capacity of 1,500 kg/24 hours and slurry ice crystal fraction about 90%. Based on consumer request, two slurry ice machine has ben made. The first one was a 1,500 kg/24 hours operated by diesel engine, while the second was a 500 kg/24 hours slurry ice machine operated by gasoline engine. Compared to the prototype unit and machine available in the commercial market, the innovation unit start producing slurry ice much faster, 2 minutes vs 20-30 minutes, and produce fraction of slurry ice crystal much higher, 90% vs 30-40%. Due to its superior quality, the practical mode of operation both by diesel oil and gasoline, and supported by ecosystem manufacture available in Indonesia, it is prospective to produce the slurry ice machine commercially.